Risk factors and clinical implications of thyroxine replacement therapy on major adverse cardiovascular events in type 2 diabetes: a retrospective cohort study - Hsu, Chih-Wei; Lin, Chia-Hung; Liu, Pi-Hua; Lin, Yi-Hsuan (Frontiers in Endocrinology, 2026)
BackgroundThyroid hormone replacement therapy is widely used to treat hypothyroidism, but there is limited research on its effects in patients with diabetes mellitus (DM). Some studies indicate that this therapy might improve lipid profiles in DM patients, but even with normalized TSH levels from thyroxine replacement, LDL and total cholesterol levels remain higher than in people with normal thyroid function. Additionally, the effect of this therapy on major adverse cardiovascular events (MACE) in DM patients is still uncertain.AimThis retrospective study investigated the occurrence of major adverse cardiovascular events (MACE) in participants receiving thyroxine with diabetes and compared the risk factors between the MACE and non-MACE groups.MethodsWe used longitudinal claims data from 2008 to 2017 from the Chang Gung Research Database. Individuals with diabetes who used thyroxine were included. The primary outcome was the occurrence of MACE. The secondary outcomes were the differences between the two groups (MACE vs. no MACE).ResultsAfter 1:1 group matching by propensity score between MACE and non-MACE groups by sex, age, and interval of using thyroxine, there were 416 patients in each group. Patients with worse renal function (eGFR <45 ml/min/1.73 m2), hypertension, history of diabetic microvascular complications, end-stage renal disease (ESRD), coronary heart disease (CHD), heart failure, cerebrovascular accident (CVA), and diabetic foot infection had a higher risk of experiencing MACE. Free T4 had a weak positive correlation with HDL, and TSH had a weak positive correlation with LDL and a negative correlation with HDL (correlation coefficient, p-value: 0.131, 0.022; 0.124, 0.016; and -0.157, 0.003, respectively). There were no optimal cutoff points according to the receiver operating characteristic (ROC) curve analysis of the best discrimination point between TSH/free T4/LDL and MACE attack.ConclusionsIn participants receiving thyroxine with diabetes, patients with worse renal function, hypertension, history of diabetic microvascular complications, ESRD, CHD, heart failure, CVA, and diabetic foot infection had a higher risk of experiencing MACE, but peripheral artery disease (PAD) was not a significant risk of MACE.